Changes of physical capacity and soccer-related skills in young soccer players within a one-year training period - Jastrzebski, Z.; Barnat, W.; Konieczna, A.; Rompa, P.; Radziminski, L. (Baltic Journal of Health and Physical Activity, 2011)
Background: The aim of this study was to determine changes in both aerobic and anaerobic physical capacity as well as in sport-specific skills in footballers as a result of the applied training load within a one-year training period. It was assumed that the type of applied training load would have a significant influence on changes in physical capacity indexes and on differences in soccer technical skills.